2009
DOI: 10.1111/j.1475-097x.2009.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintained cerebral metabolic ratio during exercise in patients with β‐adrenergic blockade

Abstract: During exhaustive exercise in cirrhotic patients the CMR is maintained and a significant cerebral uptake of lactate is demonstrated. The data suggest that oral treatment with a non-selective beta-adrenergic receptor antagonist attenuates cerebral non-oxidative metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Part of the reduction in CMR O2 /CMR glc ratio during brain activation may also reflect retention of some glucose in tissue by (i) an increase in lactate, (ii) use of glucose for glycogen synthesis, and (iii) increased pyruvate carboxylation (Öz et al, 2004) leading to enhanced glutamate formation (Gibbs et al, 2007; Mangia et al, 2012). The reduced CMR O2 /CMR glc ratio during exercise is also inhibited by propranolol (Quistorff et al, 2008; Gam et al, 2009). …”
Section: Influence Of Noradrenaline On Lactate Traffickingmentioning
confidence: 99%
“…Part of the reduction in CMR O2 /CMR glc ratio during brain activation may also reflect retention of some glucose in tissue by (i) an increase in lactate, (ii) use of glucose for glycogen synthesis, and (iii) increased pyruvate carboxylation (Öz et al, 2004) leading to enhanced glutamate formation (Gibbs et al, 2007; Mangia et al, 2012). The reduced CMR O2 /CMR glc ratio during exercise is also inhibited by propranolol (Quistorff et al, 2008; Gam et al, 2009). …”
Section: Influence Of Noradrenaline On Lactate Traffickingmentioning
confidence: 99%
“…For the sake of consistency, only data collected using the same experimental methods and only publications where data were presented comprehensively, i.e., in a table, were included. Of those, 8 were patients with cirrhosis (23), while the remaining 88 were young, healthy volunteers. The included publications are presented in Table 1.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Brachial arterial (4,8,9,13,(23)(24)(25), or radial arterial (22), and jugular venous blood gases and metabolite concentrations were determined on a Radiometer ABL 700 series (Radiometer Medical, Brønshøj, Denmark) in all studies. A measure of global CBF was derived from changes in transcra- nial ultrasound Doppler flow velocity.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Thus, the incidence of POCD with nitroglycerine is higher than that with nicardipine. In this study, the incidences of POCD were the same in Groups A and B, while those in Groups C and D showed no significant difference, thereby suggesting that esmolol may produce no effect on cerebral metabolism 20,21 . In addition, although the use of nicardipine entails the risk of intracranial hemorrhage by dilating cerebrovascular blood vessels to increase baseline rCBF, none of the patients in this study developed intracranial hemorrhage.…”
Section: 5±324 ----------------------mentioning
confidence: 63%
“…Li et al 19 found that treatment with calcium channel antagonists may protect against neuronal damage, improve cognitive function, and delay cognitive dysfunction. Calcium channel antagonists have been found to influence cerebral metabolism, and beta-receptor blockers have been shown to have no effect on OCI 16,20,21 . Several studies have shown that the uptake of lactate and glucose reduces OCI 22,23 .…”
mentioning
confidence: 99%